Universally speaking: Lost in Translation and polyglot cinema - Dwyer, Tessa (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Conceived from the start as a cultural form with mass, international appeal, cinema bears a fascinating relationship to translation, both real and figurative. From the days of the silents and early talkies to contemporary new Hollywood, this paper explores the nature of this relationship through reference to Lost in Translation and the wider polyglot genre. Revelling in the comic and poetic potential of inter-cultural (mis)communication, Lost in Translation (2004) directs attention towards the messy and mundane realities of translation, thereby exposing the industry’s more usual predilection to ignore or disavow the complexities of language difference. Comparing Lost in Translation to cinematic predecessors such as Le Mépris / Contempt (1963) and 1930s polyglots, this discussion seeks primarily to challenge the myth that the language of cinema is universal.